Pelatihan dan Pendampingan Aplikasi E-Kinerja Bagi Guru Sekolah Dasar untuk Meningkatkan Efektivitas Administrasi Kinerja - Hariandi, Ahmad; Eka Putri, Andi Gusmaulia; Zahyuni, Violita; Sholeh, Muhammad; Novianti, Silvina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service activity was conducted at SDN 56/I Aro Village with the aim of improving teacher competency in using the E-Kinerja application to support effective performance administration. This topic was chosen based on the low technology utilization in partner schools and the limited skills of teachers in managing digital administration. The activity was implemented through a preliminary survey, training, mentoring, and evaluation stages, involving the principal and teachers as active participants. The results of the activity showed an increase in teacher understanding and skills in operating the E-Kinerja application, starting from logging in, filling out performance planning, and synchronizing data. Continuous mentoring also increased teacher independence and confidence in dealing with technical obstacles. Thus, this activity successfully supported the digitalization of performance administration in elementary schools and can serve as a model for other schools to improve the effectiveness of technology-based performance management.